FPGA based real time fuzzy fault detection algorithm - Aydin, Ilhan; Karakose, Mehmet; Akin, Erhan (My University, 2010)
This paper presents a fast fuzzy algorithm, implemented using field-programmable gate array (FPGA) to detect the stator related faults in induction motors. Altera Cyclone III FPGA was employed for developing the proposed method. All coding of fuzzy algorithm was written using hardware description language (HDL) called very high speed integrated circuit description language (VHDL). Fuzzy system has three inputs and one output. The magnitudes of three phase current signals were given to the fuzzy system and stator related faults were detected. The validity of the proposed method was tested by experimental data set and was also compared to the results of MATLAB fuzzy logic toolbox. The experimental results show that the proposed method gives very efficient and reliable results for fault detection of induction motors. © 2010 IEEE.
2010 International Conference of Soft Computing and Pattern Recognition, SoCPaR 2010 -- 7 December 2010 through 10 December 2010 -- Cergy-Pontoise -- 83752
Keywords: Fault detection and diagnosis; Filed-programmable gate array (FPGA) implementation; Fuzzy logic; Induction motors; VHDL